Influencing and meeting international standards : challenges for developing countries (ITC GenevaCH, 2003)
Examines the difficulties hindering the export efforts of developing countries due to shortcomings in their standardization and conformity assessment infrastructure. Presents an inventory of the technical assistance needs of developing countries in relation to technical regulations and sanitary and phytosanitary measures.
Contents: v.1. Background information, findings from case studies and technical assistance needs. - v. 2. Procedures followed by selected international standard-setting organizations and country reports on TBT and SPS.